The brain [videorecording (DVD)] - Vagg, Richard; Thompson, Erik, 1959- (History : Marketed and distributed in the U.S. by New Video, 2008)
"Using simple analogies, real-life case studies, and state-of-the art CGI, this special shows how the brain works, explains the frequent battle between instinct and reason, and unravels the mysteries of memory and decision-making. It takes us inside the mind of a soldier under fire to see how decisions are made in extreme situations, examines how an autistic person like rain Man develops remarkable skills, and takes on the age-old question of what makes one person good and another evil"--Container.